PC alloy with hardened surface through microwave curing and preparation method
By adding methacrylate to the PC resin and cross-linking it with the epoxy chain extender using microwave action, the problem of improving the surface hardness of PC resin in the prior art is solved, and the effect of efficiently improving the surface hardness is achieved, while maintaining the original properties of the resin.
Patent Information
- Application Number
- CN202510001430.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The prior art is difficult to efficiently improve the surface hardness of PC resins, and common methods have problems such as complex processes, serious pollution, high costs or affecting the performance of the resin.
The surface hardness is improved by adding methacrylate to the PC resin and migrating it to the finished product surface during the injection molding process, while cross-linking with the epoxy chain extender using microwave action.
The surface hardness of PC products has been significantly improved to 2H-3H without affecting the mechanical and thermal properties of PC resin.
Smart Images

Figure BDA0005225329750000021 
Figure BDA0005225329750000031 
Figure BDA0005225329750000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of PC alloy plastics, and in particular relates to a microwave-cured surface-hardened PC alloy and a preparation method thereof. Background Art
[0002] Polycarbonate (PC) is a widely used engineering plastic, with applications in 3C, wall opening, home appliances, automotive interiors, etc. However, the surface hardness of PC resin itself is not high, and it is easy to be scratched and leave scratches during production, transportation, and use. Therefore, research on improving the performance hardness of PC resin is very important. The pencil hardness of commercially available general-purpose polycarbonate is around 3B. Currently, the industry mainly uses two methods to improve the hardness of PC products. One is to spray paint, which involves complex processes, serious pollution and high costs; the other is to blend polymethyl methacrylate, which has limited hardness improvement, and a high content of polymethyl methacrylate will seriously affect the flame retardant properties and toughness of PC products.
[0003] At present, the main methods for improving the surface hardness of PC on the material side are adding anti-scratch agents, blending polymethyl methacrylate, etc. Patent CN101812225A discloses a flame-retardant polycarbonate material with high surface hardness and glossiness and a preparation method, which improves the surface hardness of the material by adding a high content of polymethyl methacrylate. The content of polycarbonate and polymethyl methacrylate is 4:1, which will greatly affect the rigidity and toughness of the polycarbonate material, making it difficult to achieve industrialization and production application.
[0004] In summary, there is an urgent need to solve the problem of efficiently improving the surface hardness of PC resin without affecting the original performance of the resin. Summary of the invention
[0005] In view of the deficiencies in the prior art, one of the purposes of the present invention is to provide a PC alloy material, which can effectively improve the surface hardness of PC resin without affecting the original properties of the resin.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0007] A PC alloy material, wherein the raw materials of the PC alloy material comprise the following components in parts by mass:
[0008]
[0009]
[0010] The hardness of PC resin itself is relatively low, and there are two main types of existing hardening technologies: one is to apply a hard coating, and the other is to add a high proportion of high-hardness resin, which has problems such as complicated process, high pollution and affecting the performance of PC substrate. The inventors have found that this problem can be solved in two ways: on the one hand, methacrylate is added, and it is migrated to the surface of the finished product during the injection molding process through a high-temperature injection molding method, reducing the impact on the performance of the PC substrate; on the other hand, through the action of microwaves, cross-linking with epoxy chain extenders occurs on the surface of the product, greatly improving the hardness. This achieves high surface hardness of PC products without affecting the original mechanical and thermal properties of PC resin.
[0011] In one embodiment of the present invention, the PC resin is one or more of aromatic polycarbonate, aliphatic polycarbonate, aromatic-aliphatic polycarbonate, preferably bisphenol A polycarbonate, more preferably one or more of Wanhua Chemical 2070, 2100, 2150, 2220, 2350. For example, the polycarbonate is required to have a melt flow index MFR between 5-50 g / 10 min, preferably between 10-30 g / 10 min, under the test conditions of 300° C. and a load of 1.2 kg.
[0012] In one embodiment of the present invention, the epoxy chain extender is an organic substance with 8-20 epoxy functional groups, preferably a copolymer of styrene-methyl methacrylate-glycidyl methacrylate, more preferably one or more of the chain extenders ADR4468, ADR4370, and ADR4400.
[0013] In one embodiment of the present invention, the catalyst is one or more of bis(boron trifluoride)bis(diphenyl)cobalt oxime, bis(boron trifluoride)bis(dimethyl)cobalt oxime, and bis(boron trifluoride)bis(dicyclohexyl)cobalt oxime.
[0014] The present invention also contains auxiliaries known in the art, such as antioxidants, the content of which can be 0.1-1 parts, preferably 0.2-0.5 parts; the antioxidant can be a combination of one or more of hindered phenols, benzofurans, acryl-modified phenols, and hydroxylamines; preferably one or more of hindered phenols; more preferably, one or more of BASF's antioxidants Irganox 1076, Irganox 1010, and Irganox 168. The auxiliaries such as antioxidants and their addition amounts are known in the art.
[0015] In one embodiment of the present invention, the methacrylate is liquid α-methacrylate and / or ethyl methacrylate, preferably liquid α-methacrylate with a purity of ≥99.5%.
[0016] Another object of the present invention is to provide a method for preparing a PC alloy material.
[0017] A method for preparing a PC alloy material, wherein the material is the above-mentioned PC alloy material, and the preparation method comprises the following steps:
[0018] S1: After the catalyst, PC resin and additives are mixed, the mixture is fed into the extruder through the main feed;
[0019] S2: feeding methacrylate into the middle section of the extruder;
[0020] S3: adding epoxy chain extender from the end feed of the extruder;
[0021] S4: melting, extruding, and granulating to obtain pellets of PC alloy material.
[0022] For example, the above preparation process may involve the following reactions:
[0023]
[0024] In one embodiment of the present invention, the catalyst, PC resin and additives in S1 are mixed using a high-speed mixer, preferably with a mixing speed of 300-900 rpm and a mixing time of 100-400 s.
[0025] In one embodiment of the present invention, the middle section of S2 is the 3rd to 4th section barrel of the extruder.
[0026] In one embodiment of the present invention, the last section of S3 is the 6th to 7th section barrel of the extruder.
[0027] In one embodiment of the present invention, the extrusion temperature of S4 is 250-300°C, and the screw speed is 300-800rpm; preferably, the extrusion temperature is set in sections from the feed port to the die head: 250-260°C at the feed port, 280-300°C for sections one to four, and 250-280°C for sections five to seven.
[0028] In the present invention, for example, the vacuum degree of the vacuum pumping device of the twin-screw metering section can be controlled to be less than -0.8 bar, and the temperature of the cooling water tank can be 30-80° C. The process is a commonly used control process in the art.
[0029] Another object of the present invention is to provide a use of a PC alloy material.
[0030] A use of a PC alloy material, wherein the material is the PC alloy material mentioned above, or is the PC alloy material prepared by the above preparation method, and the material is used for electronic and electrical products, household appliances, and digital products.
[0031] Another object of the present invention is to provide a method for preparing a PC product.
[0032] A method for preparing a PC product, wherein the product adopts the PC alloy material mentioned above, or the PC alloy material prepared by the preparation method mentioned above, and the method comprises: after the product is obtained by injection molding, microwave curing is performed; preferably, the barrel temperature of the injection molding machine for the injection molding is set to 300-320°C, the injection pressure is 60-80MPaG, the mold temperature is 110-130°C, and the holding time is 1-3s; preferably, the power of the microwave curing is 100-500W, the irradiation temperature is 80-100°C, and the irradiation time is 1-3min.
[0033] Compared with the prior art, the present invention has the following positive effects:
[0034] (1) The hardness is greatly improved to 2H-3H.
[0035] (2) Does not affect the original mechanical and thermal properties of PC resin. DETAILED DESCRIPTION
[0036] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0037] 1. In the embodiments and comparative examples, the sources of the main raw materials are shown in Table 1 below:
[0038] Table 1 Raw material source information
[0039]
[0040]
[0041] Unless otherwise specified, other raw materials and reagents were purchased from commercial sources.
[0042] 2. In the embodiments and comparative examples, the performance test parameters and corresponding test methods of PC alloys are as follows:
[0043] The processing equipment used was: twin-screw extruder: KraussMaffei ZE28 x40D BD, with an aspect ratio of 40 and a screw diameter of 28 cm;
[0044] The performance test parameters and corresponding test methods of PC alloy are as follows:
[0045] Pencil hardness: GB 6739-86 "Coating Hardness Pencil Hardness Method" is adopted;
[0046] Flexural strength and modulus (MPa): ISO 178:2010 "Plastics - Determination of flexural properties";
[0047] Impact strength (MPa): Tested according to ISO 180-2000 "Determination of Izod impact strength of plastics";
[0048] Heat deformation temperature (℃): Tested using ISO 75 / B "Test method for heat deformation temperature of plastics".
[0049] Example 1
[0050] The microwave-cured surface-hardened PC alloy was prepared using the following raw material formula:
[0051]
[0052] The preparation method is:
[0053] a. Mix the catalyst, PC resin and antioxidant in a high-speed mixer at a mixing speed of 600 rpm and a mixing time of 200 s;
[0054] b. feeding the mixture of step a) from the main feed of the extruder;
[0055] c. Add α-methacrylate liquid into the 3-stage barrel from the side feed;
[0056] d. Add epoxy chain extender ADR4468 from the feeding port of the last 6-stage barrel;
[0057] e. Extrusion conditions: control the vacuum degree of the vacuum device of the twin-screw metering section to be less than 0.08MPa, the screw speed is 500rpm, and the screw temperature from the feed port to the die is set to 255℃, 290℃, 290℃, 290℃, 290℃, 265℃, 265℃, 265℃;
[0058] f. Cool the extruded material at 50°C in the water tank of the extruder and pelletize it;
[0059] g. Injection molding the particles in step f) into a sample under the conditions of injection temperature of 300° C., injection pressure of 60 MPa, mold temperature of 110° C., and holding pressure of 1 second;
[0060] h. Place the sample in step g) under microwave power of 100 W and temperature of 80° C. for 1 min to obtain a PC alloy with a hardened surface.
[0061] Example 2
[0062] The microwave-cured surface-hardened PC alloy was prepared using the following raw material formula:
[0063]
[0064] The preparation method is:
[0065] a. Mix the catalyst, PC resin and antioxidant in a high-speed mixer at a mixing speed of 300 rpm and a mixing time of 400 s;
[0066] b. feeding the mixture of step a) from the main feed of the extruder;
[0067] c. Add α-methacrylate liquid into the 4-stage barrel from the side feed;
[0068] d. Add epoxy chain extender ADR4370 from the feeding port of the last 7-stage barrel;
[0069] e. Extrusion conditions: control the vacuum degree of the vacuum device of the twin-screw metering section to be less than 0.08MPa, the screw speed to be 300rpm, and the screw temperature from the feed port to the die to be set in sections to: 250℃, 280℃, 280℃, 280℃, 280℃, 250℃, 250℃, 250℃;
[0070] f. Cool the extruded material at 80°C in the water tank of the extruder and pelletize it;
[0071] g. Injection molding the particles in step f) into a sample under the conditions of injection temperature of 320° C., injection pressure of 80 MPa, mold temperature of 130° C., and holding pressure of 3 seconds;
[0072] h. Place the sample in step g) under microwave irradiation at a power of 500 W and a temperature of 100° C. for 3 min to obtain a surface-hardened PC alloy.
[0073] Example 3
[0074] The microwave-cured surface-hardened PC alloy was prepared using the following raw material formula:
[0075]
[0076] The preparation method is:
[0077] a. Mix the catalyst, PC resin and antioxidant in a high-speed mixer at a mixing speed of 900 rpm and a mixing time of 100 s;
[0078] b. feeding the mixture of step a) from the main feed of the extruder;
[0079] c. Add α-methacrylate liquid into the 3-stage barrel from the side feed;
[0080] d. Add epoxy chain extender ADR4400 from the feeding port of the last 7-stage barrel;
[0081] e. Extrusion conditions: control the vacuum degree of the vacuum device of the twin-screw metering section to be less than 0.08MPa, the screw speed to be 800rpm, and the screw temperature from the feed port to the die to be set in sections as: 260℃, 300℃, 300℃, 300℃, 300℃, 280℃, 280℃, 280℃;
[0082] f. Cool the extruded material at 30°C in the water tank of the extruder and pelletize it;
[0083] g. Injection molding the particles in step f) into a sample under the conditions of injection temperature of 310° C., injection pressure of 70 MPa, mold temperature of 120° C., and holding pressure of 2 seconds;
[0084] h. Place the sample in step g) under microwave power of 300 W and temperature of 90° C. for 2 min to obtain a PC alloy with a hardened surface.
[0085] Comparative Example 1
[0086] Compared with Example 1, the only difference is that no epoxy chain extender is added.
[0087] Comparative Example 2
[0088] Compared with Example 1, the only difference is that no methacrylate liquid is added.
[0089] Comparative Example 3
[0090] Compared with Example 1, the only difference is that no methacrylate liquid and epoxy chain extender are added.
[0091] Comparative Example 4
[0092] Compared with Example 1, the only difference is that the α-methacrylate liquid is not added and is replaced by the same mass of polymethyl methacrylate resin HD01.
[0093] The relevant properties of the PC alloys obtained in Examples 1-3 and Comparative Examples 1-4 are shown in Table 2.
[0094] Table 2 Performance test results of products of Examples 1-3 (S1-S3) and Comparative Examples 1-4 (D1-D4)
[0095]
[0096]
[0097] It can be seen from comparative examples 1-4 and examples 1-3 that the PC alloys in the examples have higher surface hardness, and the mechanical properties and thermal properties of the PC alloys are well maintained. However, the comparative examples have the disadvantages of low toughness, reduced strength, and reduced heat resistance.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A PC alloy material, characterized in that: The raw materials of the PC alloy material include the following components in parts by mass: PC resin 86-98 parts, preferably 90-95 parts, Epoxy chain extender 0.5-2 parts, preferably 1-1.5 parts, Catalyst 0.1-1 part, preferably 0.4-0.6 part, Methacrylate 2-10 parts, preferably 5-10 parts.
2. The material according to claim 1, characterized in that The PC resin is one or more of aromatic polycarbonate, aliphatic polycarbonate, and aromatic-aliphatic polycarbonate, preferably bisphenol A polycarbonate, and more preferably one or more of Wanhua Chemical 2070, 2100, 2150, 2220, and 2350.
3. The material according to claim 1 or 2, characterized in that The epoxy chain extender is an organic substance with 8-20 epoxy functional groups, preferably a copolymer of styrene-methyl methacrylate-glycidyl methacrylate, more preferably one or more of the chain extenders ADR4468, ADR4370, and ADR4400.
4. The material according to any one of claims 1 to 3, characterized in that The catalyst is one or more of bis(boron trifluoride)bis(diphenyl)cobalt oxime, bis(boron trifluoride)bis(dimethyl)cobalt oxime and bis(boron trifluoride)bis(dicyclohexyl)cobalt oxime.
5. The material according to any one of claims 1 to 4, characterized in that The methacrylate is liquid α-methacrylate and / or ethyl methacrylate, preferably liquid α-methacrylate with a purity of ≥99.5%.
6. A method for preparing a PC alloy material, wherein the material is the PC alloy material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: S1: After the catalyst, PC resin and additives are mixed, the mixture is fed into the extruder through the main feed; S2: feeding methacrylate into the middle section of the extruder; S3: adding epoxy chain extender from the end feed of the extruder; S4: melting, extruding, and granulating to obtain pellets of PC alloy material.
7. The preparation method according to claim 6, characterized in that: The catalyst, PC resin and additives in S1 are mixed by a high-speed mixer, preferably with a mixing speed of 300-900 rpm and a mixing time of 100-400 s; And / or, the middle section of S2 is the 3rd-4th section barrel of the extruder; And / or, the last section of S3 is the 6th-7th section barrel of the extruder; And / or, the extrusion temperature of S4 is 250-300°C, and the screw speed is 300-800rpm; Preferably, the extrusion temperature is set in sections from the feed port to the die head: 250-260°C at the feed port, 280-300°C at sections one to four, and 250-280°C at sections five to seven.
8. Use of a PC alloy material, wherein the material is the PC alloy material according to any one of claims 1 to 5, or is the PC alloy material prepared by the preparation method according to claim 6 or 7, and the material is used for electronic and electrical products, home appliances, and digital products.
9. A method for preparing a PC product, wherein the product is made of the PC alloy material according to any one of claims 1 to 5, or a PC alloy material prepared by the preparation method according to claim 6 or 7, characterized in that: The method comprises: after the product is obtained by injection molding, microwave curing is performed; Preferably, the barrel temperature of the injection molding machine for injection molding is set at 300-320°C, the injection pressure is 60-80MPaG, the mold temperature is 110-130°C, and the holding time is 1-3s; Preferably, the power of the microwave curing is 100-500 W, the irradiation temperature is 80-100° C., and the irradiation time is 1-3 min.
Citation Information
Patent Citations
Flame retardant polycarbonate material with high surface hardness and gloss and preparation method thereof
CN101812225A
Polycarbonate alloy composite material with adjustable surface hardness and preparation method thereof
CN112480634A
High-hardness PC alloy and preparation method thereof
CN118930874A
Photocurable hard coat composition for plastic substrates and hard coat film
JP2018109158A
Polycarbonate resin composition having improved transparency and scratch-resistance and product thereof
KR101813399B1